Estimación del contenido de carbono en biomasa en la plantación de teca (Tectona grandis), ubicado en la comuna de San Pablo, sector Río Basura, cantón Joya de los Sachas, parroquia San Sebastián del Coca, provincia de Orellana - Andi Grefa, Lizbeth Clelia (2015)
The objective of this research, conducted in a teak plantation (Tectona grandis Linn F.) located in the San Pablo commune, is intended to assess the impact socio economic and environmental, this type of project generated in inhabitants, as an alternative of revenue in addition to wood, estimating the content of carbon in biomass of the plantation, and propose a Plan of environmental management; to assess the impact of socio-economic and environmental surveys were conducted, results that were tabulated and represented by figures and statistical tables. For the quantification of biomass carbon was a systematic forest inventory at an intensity of sampling of the 1,5%, setting 4 500 m² plots distributed on 12,85 acres, the volume of wood from plantation, was determined to know the density, was felled 2 trees in which were obtained samples; taking samples on the basis of the standard INEC 11.60; in the basal and apical, central part of the trunk, which is taken to the laboratory to determine its density, applied the allometric equation allowing to estimate the biomass of plantation; The results of this process indicate that a plantation of Teak from four years in the commune Saint Paul, has a volume of 32,46m³ha; 66,12tonha of aboveground biomass and 33,06tonha, of stored carbon, which constitutes a great significant carbon storage so it is recommended the use of the species for reforestation purposes